The Comparative Study of the Quranic Researching Approach of “Āmina Wadud” and “ʿĀʾisha Bint al-Shāṭi” (by Emphasis on the Fundamentals and Methods) - Ibrahim Ibrahimi; Fatimah Dastranj (آموزه‌های قرآنی)
Knowing the approaches of the commentators (the scholars who interpret the Holy Book of Quran) of Quranic researching provides the basis for understanding, analyzing and criticizing their views and opinions, because tafsīr (Arabic: تفسیر, exegesis) texts are influenced by the commentator’s worldview and mental ideas, as well as a reflection of the cultural and social requirements of his era. One of the issues that has recently become a subject in the field of understanding and interpreting the Holy Book of Quran is the effect of gender element in the understanding of religious texts. Therefore, this research, using descriptive-analytical method in a comparative context, has investigated the tendency, Fundamentals and exegetical methods of “Āmina Wadud” (Arabic: آمنة ودود) and “ʿĀʾisha Bint al-Shāṭi” (عائشة بِنت الشاطئ) two of the Quran researchers. The obtained results indicate that the interpretative tendency of Āmina Wadud is social, transsexual and justice-oriented. She has used the hermeneutic method and philosophical analysis in explaining the discourses of the Qur'an in this regard. The tendency of the fundamentals and methods in the Quranic understanding of Āmina Wadud in her social commentary leads her to Islamic rulings in the field of women in order to present a new and modern reading of them. But Bint al-Shāṭi’s exegesis tendency is theological literary in line with the Quran’s verbal inimitability (Arabic: الإِعجاز البیانیّ, Romanized: al-Iʾjāz) of the Holy Book of Quran. She is trying to put emphasis and style (the methods used in written language) on the verbal inimitability of the Holy Book of Quran by a linguistic point of view in line with the method of verbal exegesis.